Socio-emotional education: paths to inspire studies, research and practices - Cordeiro, Eugenia de Paula Benício (2021)
This article presents findings of a bibliographic research which had as its scope identifying social and emotional skills proposed by different authors from this field. More specifically, it aimed to: classifying social and emotional skills by domains of competencies; detailing the skills related to self-awareness, focusing on the emotional dimension; proposing a lesson plan for promoting self-awareness in the classroom. The findings have shown that: by detailing social and emotional skills per competence, it may contribute to guide pedagogical activities based on theoretical pinpoints; deepening the theoretical foundations of emotions is essential for understanding the process of self-awareness; creating pedagogical sequences coherent and consistent with social and emotional development, requires the exercise of transposing theory into practice, respecting each educator’s singularities according to his/her reality in class.